Teaching at home : a new approach to tutoring children with autism and Asperger syndrome - Holland, Olga, 1957- (Jessica Kingsley Publishers, 2005)
Faced with the apparent inability of her autistic son Billy to learn and socialize with other children at school, Olga Holland decided to teach him at home. Where traditional educational approaches had produced limited results, the author's own method of teaching succeeded, over a period of two years, in enabling Billy to pass the test that allowed him to enter a class for gifted children. Teaching at Home explains the author's approach, focused on adapting to the demands of Billy's atypical mind and respecting his vivid imaginative world while attracting and retaining his attention. The autho.